Nilai Perusahaan Ditinjau dari Dewan Komisaris Independen dan Komite Audit dengan Profitabilitas sebagai Variabel Moderasi - Widia Gustina; Aminar Sutra Dewi (Lembaga Yasin AlSys, 2025)
Firm value is a key indicator reflecting investors’ perceptions of a company’s performance and long-term prospects. This study aims to analyze the effect of independent commissioners and audit committees on firm value, as well as the moderating role of profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2022. A quantitative approach was employed, using purposive sampling to select a sample of 24 companies, resulting in 96 observations over four years. Data were analyzed using panel data regression with the assistance of Eviews 12 software. The findings reveal that independent commissioners have no significant effect on firm value, while audit committees have a positive and significant effect. Profitability also has a positive and significant effect on firm value. Moreover, profitability moderates the relationship between independent commissioners and firm value, but does not moderate the relationship between audit committees and firm value. These results highlight the importance of audit committee effectiveness and profitability in shaping investor perceptions of firm value, and they offer implications for strengthening corporate governance through effective internal oversight and financial performance.